COGNITIVE-AFFECTIVE ASPECTS OF FORMING BRAND LOYALTY - Shanti, Mardhatillah; Sunaryo, Sunaryo; Rofiq, Ainur (Universitas Brawijaya, Indonesia, 2019)
This study has the aims to determine both direct and indirect effects of brand experience, brand satisfaction, brand love dan brand loyalty to Wardah cosmetic's consumers in Malang City. 160 samples were taken by using the nonprobability approach with purposive sampling technique. Data was collected through questionnaires and analyzed using SmartPLS 3.0. Respondents were above 15 years of age and had bought and used Wardah cosmetics more than once. The result found that brand experience has no significant effect on brand loyalty. Furthermore, brand satisfaction and brand love are found as a full mediation to the effect of brand experience on brand loyalty. For further research are recommended to use more than one cosmetic brand as the object of the research, to provide more representative results.